Le futurisme polonais, 1918-1924 poésie, manifestes, déclarations = Polski futuryzm, 1918-1924 : poezje, manifesty, deklaracje - Jedrzejewski, Franck 1958-; Perigot-Grygielewicz, Malgorzata 1978- (Brill, 2025)
"In the history of the twentieth century, Futurism marked the birth of the avant-garde and major artistic and literary changes. Although it first appeared in Italy and Russia, it developed in Poland between 1918 and 1929. The vast documentation and texts, most of them previously unpublished, that we have brought together in this volume constitute the most complete collection ever published on Polish Futurism. A rich critical apparatus and iconography from the 1920s complete the work"--
Keywords: Lyrik; Künstlerisches Manifest; Polnisch; Futurismus; Futurism (Literary movement) / Poland; Polish poetry / 20th century / History and criticism; Literary criticism; Essays; Anthologie